Frame analysis : an essay on the organization of experience - Goffman, Erving (Northeastern University Press, 1974)
Erving Goffman will influence the thinking and perceptions of generations to come. In Frame Analysis, the brilliant theorist writes about the ways in which people determine their answers to the questions “What is going on here?” and “Under what circumstances do we think things are real?”